How Do Dinosaurs Learn to Be Kind? - Yolen, Jane; Teague, Mark (New York : Scholastic Press, 2023)
It is not always easy for a dinosaur to learn how to be kind, but with a liitle practice, and keeping other people firmly in mind, he can become a one-of-a-kind, very kind dinosaur.
New Kids Book 2023 Winter.
Ages 3-5.
Grades K-1.
Keywords: Dinosaurs -- Juvenile fiction; Kindness -- Juvenile fiction; Thoughtfulness -- Juvenile fiction; Stories in rhyme; Kindness -- Fiction; Dinosaurs -- Fiction; JUVENILE FICTION / Animals / Dinosaurs & Prehistoric Creatures; JUVENILE FICTION / Humorous Stories; Stories in rhyme; Picture books